Maximizing bidder’s profit in online auctions using grey system theory predictor agent - Deborah Lim; Patricia Anthony; Ho, Chong Mun (Emerald Group Publishing Limited, 2012)
Purpose – As the demand for online auctions increases, the process of monitoring multiple auction houses, deciding which auction to participate in and making the right bids, become challenging tasks for consumers. Hence, knowing the closing price of a given auction would be an advantage, since this information will ensure a win in a given auction. However, predicting a closing price for an auction is not easy, since it is dependent on many factors. The purpose of this paper is to report on a predictor agent that utilises grey system theory to predict the closing price for a given auction.